Status and effect of fascioliasis in buffaloes kept extensively in a farm in Sabah, Malaysia - Noorzahari, Mohd Ridzuan; Saad, Mohd Zamri; Abdullah Sani, Rehana (2012)
This study was carried out to determine the status and possible effect of fascioliasis among buffaloes kept extensively in the Buffalo Breeding and Research Centre at Telupid, Sabah, Malaysia. Forty adult four-year old buffaloes from a herd of 250 animals were selected for the study. Faecal samples were obtained from the animals and subjected to sedimentation technique to determine the presence of Fasciola sp. ova. Blood sample from each animal was collected into a plain tube and serum obtained for determination of AST and albumin concentrations. The helminth burden was determined in these animals to obtain information on the prevalence of gastrointestinal helminthiasis in the farm. None of the faecal samples had Fasciola sp. ova. However, the serum ALT concentrations in these animal were significantly (p<0.05) higher than the upper limit of the reference range. The study suggests that that the buffaloes may have been exposed to diseases that caused liver damage.